An activity gradient of decapentaplegic is necessary for the specification of dorsal pattern elements in the Drosophila embryo. - Wharton, K.A.; Ray, R.P.; Gelbart, W.M. (Development, 1993)
decapentaplegic (dpp) is a zygotically expressed gene encoding a TGF-beta-related ligand that is necessary for dorsal-ventral patterning in the Drosophila embryo. We show here that dpp is an integral part of a gradient that specifies many different cell fates via intercellular signalling. There is a graded requirement for dpp activity in the early embryo: high levels of dpp activity specify the amnioserosa, while progressively lower levels specify dorsal and lateral ectoderm. This potential for dpp to specify cell fate is highly dosage sensitive. In the wild-type embryo, increasing the gene dosage of dpp can shift cell fates along the dorsal-ventral axis. Furthermore, in mutant embryos, in which only a subset of the dorsal-ventral pattern elements are represented, increasing the gene dosage of dpp can specifically transform those pattern elements into more dorsal ones. We present evidence that the zygotic dpp gradient and the maternal dorsal gradient specify distinct, non-overlapping domains of the dorsal-ventral pattern.